Degradation of non-vulcanized natural rubber - renewable resource for fine chemicals used in polymer synthesis - Fainleib,Alexander (2013)
In the current scenario, there is growing interest in the products of degradation of rubber (natural and synthetic) for specific applications in different industry sectors, whose benefits in replacing conventionally used products are mainly related to sustainability. Since the degradation products of rubber can be used in different areas, several research groups may have the interest aroused by these products, but are not familiar with the aspects related to the chemical behavior of rubber. This review aims to bring together the key information in the published literature on the degradation of natural rubber, emphasizing metatheses reactions, oxidative damage and splitting of the double bond, in order to serve as a reference source for researchers from different fields interested in obtaining such kind of products. The structures and properties as well as additional chemical transformations resulting in oligomers of isoprene, functionalised oligomers and polymers based on both are also described.